2015
DOI: 10.1016/j.talanta.2014.07.086
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the use of anthocyanin profile, color image analysis and near-infrared hyperspectral imaging as tools to discriminate between four autochthonous red grape cultivars from La Rioja (Spain)

Abstract: a b s t r a c tThree independent methodologies were investigated to achieve the differentiation of red grapes from different grape varieties (Garnacha, Graciano, Mazuelo and Tempranillo) collected from five vineyards located in the D.O.Ca. Rioja. Anthocyanin chromatographic analysis, color image analysis and near infrared hyperspectral imaging were carried out for the grapes. Then, a Stepwise Linear Discriminant Analysis (SLDA) was developed for each data set in order to discriminate grapes according to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 19 publications
2
11
1
2
Order By: Relevance
“…The major acylated form in Carignan noir grapes was the coumaroylated, which has already been shown for this variety by Fernandes de Oliveira et al . With respect to non‐acylated forms, malvidin‐3‐glc was the most abundant anthocyanin, followed by delphinidin‐3‐glc and petunidin‐3‐glc, being the less abundant cyanidin‐3‐glc, confirming previous results showed by Nogales‐Bueno et al . Total anthocyanins ranged from 1582.59 to 2271.31 mg kg −1 , corresponding to the grapes from Cdn and Sau sites, respectively, being greater than those observed by Jensen et al .…”
Section: Resultssupporting
confidence: 87%
“…The major acylated form in Carignan noir grapes was the coumaroylated, which has already been shown for this variety by Fernandes de Oliveira et al . With respect to non‐acylated forms, malvidin‐3‐glc was the most abundant anthocyanin, followed by delphinidin‐3‐glc and petunidin‐3‐glc, being the less abundant cyanidin‐3‐glc, confirming previous results showed by Nogales‐Bueno et al . Total anthocyanins ranged from 1582.59 to 2271.31 mg kg −1 , corresponding to the grapes from Cdn and Sau sites, respectively, being greater than those observed by Jensen et al .…”
Section: Resultssupporting
confidence: 87%
“…This is the first study where NIR spectroscopy has been applied to the prediction of EL, ChlC, and E. In this study, the statistical parameters reported for SECV, SEP, SLOPE, and RSQ, were similar to the ones previously obtained in other studies where NIR-based technology was used in oenology and viticulture [55][56][57]61,62]. This indicated that NIR spectral measurements could be suitable for predicting all four variables (Fv/Fm, EL, ChlC, and E) from a single spectral measurement.…”
Section: Discussionsupporting
confidence: 80%
“…Spectroscopy and hyperspectral imaging have also arisen in the last few years as important nondestructive methods to acquire relevant crop spectral information for phenotype characterization [52]. Among these methods, near-infrared (NIR) spectroscopy is widely used for studying different agronomic characteristics of grapevines [53], for example, grape composition [54], total phenolic compounds, anthocyanin profiles, and grape maturity [55][56][57], as well as grapevine petiole nutrient concentration [58], identification of grape berry sunburn symptoms [59], plant water status [60,61], and grapevine varietal discrimination [52,62]. Hence, NIR spectroscopy is a promising tool for precision viticulture [52] and a potentially attractive technology for screening new grapevine clones with enhanced thermotolerance in plant breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…Equipment and procedure used to image recording are described in detail in Hernández‐Hierro et al and Nogales‐Bueno et al The main components of the hyperspectral imaging device (Infaimon S.L., Barcelona, Spain) were the illumination source, optics (mirror scanner and lens), spectrograph, camera and computer. The system comprised a Xenics® XEVA‐USB InGaAs camera (320 × 256 pixels; Xenics Infrared Solutuions, Inc., Leuven, Belgium), a spectrograph (Specim ImSpector N17E Enhanced; Spectral Imaging Ltd., Oulu, Finland) covering the spectral range between 900 and 1700 nm (spectral resolution of 3.25 nm), two 70‐W tungsten iodine halogen lamps (Prilux®, Barcelona, Spain) mounted as source light, a mirror scanner (Spectral Imaging Ltd) and a computer system.…”
Section: Methodsmentioning
confidence: 99%
“…The development of hyperspectral analysis methods for use in the food sector in the recent past has risen considerably . Our previous work has demonstrated the potential of near infrared (NIR) hyperspectral imaging to discriminate between four red grape cultivars and also to quantify anthocyanins in two red grape cultivars from a warm climate with acceptable accuracy for screening purposes . As stated in the aforementioned study, factors such as grape varieties or production areas should be studied in the development of these models.…”
Section: Introductionmentioning
confidence: 99%